Are patients with hormonally functional phaeochromocytoma and paraganglioma initially receiving a proper adrenoceptor blockade? A retrospective cohort study. (15th April 2016) - Luiz, Henrique Vara; Tanchee, Mary Jane; Pavlatou, Maria G.; Yu, Run; Nambuba, Joan; Wolf, Katherine; Prodanov, Tamara; Wesley, Robert; Adams, Karen; Fojo, Tito; Pacak, Karel
Summary: Objective: Pharmacological treatment is mandatory in patients with hormonally functional phaeochromocytoma and paraganglioma (PHAEO/PGL). We evaluated if patients initially diagnosed with hormonally functional PHAEO/PGL by various medical subspecialties received proper adrenoceptor blockade, and analysed factors predicting the prescription of adequate treatment. Methods: In a retrospective cohort study, we reviewed data from patients initially diagnosed with hormonally functional PHAEO/PGL outside the National Institutes of Health and Cedars‐Sinai Medical Center, who were referred to these institutions between January 2001 and April 2015. Logistic regression was used to assess factors associated with proper adrenoceptor blockade. Results: A total of 381 patients were included. Adequate pharmacological treatment was prescribed to 69·3%, of which 93·1% received α‐adrenoceptor blockers. Regarding patients who were inappropriately treated, 53% did not receive any medication. Independent predictors of the prescription of a proper blockade were the diagnosis by endocrinologists [odds ratio (OR) 4·14; 95% confidence interval (CI), 2·51–6·85; P < 0·001], the presence of high blood pressure (OR 5·94; 95% CI, 3·11–11·33; P < 0·001) and the evidence of metastasis (OR 5·96; 95% CI, 1·93–18·46; P = 0·002). Conclusions: Although most patients received adequate pharmacological treatment, almost one‐third were either not treated or received inappropriate medications. The diagnosis by endocrinologists, the presence of high blood pressure and the evidence of metastatic disease were identified as independent predictors of a proper blockade. These results highlight the need to educate physicians about the importance of starting adequate adrenoceptor blockade in all patients with hormonally functional PHAEO/PGL.